HIGH SCHOOLS AND STUDENTS' INITIAL COLLEGES AND MAJORS. (14th May 2018) - Darolia, Rajeev; Koedel, Cory
Abstract : We use statewide administrative data from Missouri to examine the explanatory power of high schools over student sorting to colleges and majors at 4‐year public universities. We develop a "preparation and persistence index" (PPI) for each university‐by‐major cell in the Missouri system that captures dimensions of selectivity and rigor and allows for a detailed investigation of sorting. Our analysis shows that students' high schools predict the quality of the initial university, as measured by PPI, conditional on their own academic preparation, and that students from lower–socioeconomic status high schools systematically enroll at lower‐PPI universities. However, high schools offer little explanatory power over major placements within universities. ( JEL I2, J1)